2022
DOI: 10.1002/cbdv.202100830
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, Flavonoids Content and Antioxidant Activities of Tuber indicum at Different Maturity Stages

Abstract: The Chinese black truffle Tuber indicum (Ascomycota, Pezizales) is an ectomycorrhizal fungus forming hypogeous edible ascocarps. As a famous wild edible mushroom in the world, this species also attracted an increasing interest in their chemical composition and pharmacological activity. In this study, the total phenolic content, total flavonoid content and antioxidant activities of Tuber indicum collected from July to November at different maturity stages in China were analyzed. Our results showed that T. indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The experimental results indicated M. importuna could yield a wide variety of phenolics. Phenolics are the vital chemical ingredient of some culinary and medicinal mushroom, such as Phellinus pini [ 25 ], Flammulina velutipes [ 26 ], Inonotus obliquus [ 27 ], Ganoderma lucidum [ 28 ], Pleurotus citrinopileatus [ 29 ], Hypsizygus marmoreus [ 30 ], Porodaedalea chrysoloma [ 31 ], Antrodia cinnamomea [ 32 ], and Tuber indicum [ 33 ], etc. Phenolics exhibit antioxidant activity and provide health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results indicated M. importuna could yield a wide variety of phenolics. Phenolics are the vital chemical ingredient of some culinary and medicinal mushroom, such as Phellinus pini [ 25 ], Flammulina velutipes [ 26 ], Inonotus obliquus [ 27 ], Ganoderma lucidum [ 28 ], Pleurotus citrinopileatus [ 29 ], Hypsizygus marmoreus [ 30 ], Porodaedalea chrysoloma [ 31 ], Antrodia cinnamomea [ 32 ], and Tuber indicum [ 33 ], etc. Phenolics exhibit antioxidant activity and provide health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Following the method of Li et al [29] with some minor adjustments, 0.5 g of the sample was dissolved in 10 mL of ethanol and extracted twice with ultrasonic at 50 • C, 200 W (KQ-600DE, Kunshan Ultrasonic Wave Technology Corporation, Kunshan, China), in the dark for 10 min, and then centrifuged at 8000 rpm for 10 min. The supernatants were combined and diluted to a final volume of 25 mL with ethanol.…”
Section: Total Phenolics and Total Flavonoidsmentioning
confidence: 99%
“…They are rich in bioactive compounds, such as dietary fiber, polysaccharide, protein, and polyphenol . Mushrooms possess some popular biological activities, including antitumor, anti-inflammatory, antioxidant, and antimicrobial properties . In the clinical studies of cancer treatment, some mushroom supplements were found to reduce chemotherapeutic toxicity and improve quality of life .…”
Section: Introductionmentioning
confidence: 99%